The Effect of Cervical Cancer Counseling on Cervical Cancer Prevention Behavior in Women of Childbearing Age: A Literature Study - Miranti Puteri Aulia; Monica Dwi Hartanti (Jurnal Kedokteran Diponegoro, 2023)
Background: : According to World Health Organization (WHO) data, cervical cancer is the second leading cause of death worldwide . In 2020 the worldwide burden of cervical cancer is significant, there are an estimated 604,000 new infections and 342,000 deaths in 2020. Based on Riskesdas data, the prevalence of tumor/cancer, especially cervical cancer, in Indonesia ranks second with 36,633 cases, accounting for 9.2% of all cancer cases. Effective interventions at various life stages could significantly reduce global mortality from cervical cancer. Objective: This study was conducted to examine the impact of cervical cancer counseling on cervical cancer prevention behavior in women of reproductive age. Methods: Conducting a literature review of previous journal articles related to the effects of cervical cancer counseling on cervical cancer prevention behavior in women of childbearing age. Results: The results of this study indicate that cervical cancer is a significant reproductive health issue in Indonesia due to low screening coverage and lack of knowledge, resulting in late diagnosis. However, education and counseling can play a vital role in increasing awareness and promoting preventive behavior towards cervical cancer. Conclusion: Education and counseling interventions can effectively increase awareness and promote preventive behavior, this promotive and preventive behavior greatly reduces the burden of cervical cancer.